2020
DOI: 10.3389/fonc.2020.00685
|View full text |Cite
|
Sign up to set email alerts
|

Successful Anti-CLL1 CAR T-Cell Therapy in Secondary Acute Myeloid Leukemia

Abstract: Secondary acute myeloid leukemia (sAML) is a high-risk AML evolving from heterogenous prior hematological disorders. Compared to de novo AML, sAML has even worse responses to current therapy and thus is associated with lower remission rates, inferior overall survival (OS) and higher relapse rates. Many efforts have been devoted to improving the overall but with limited success, and novel strategy is thus highly needed. Recent research has identified that CLL1 is highly expressed on AML leukemia stem cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Therefore, targeting the CLEC12A antigen will target AML blasts and leukemic stem cells while sparing normal hematopoiesis. Several groups have advanced CLEC12A-targeting CAR T cells into clinical trials (30,31). Our results demonstrate that targeting CLEC12A eliminates AML cells in vitro and significantly reduces tumor burden in vivo.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, targeting the CLEC12A antigen will target AML blasts and leukemic stem cells while sparing normal hematopoiesis. Several groups have advanced CLEC12A-targeting CAR T cells into clinical trials (30,31). Our results demonstrate that targeting CLEC12A eliminates AML cells in vitro and significantly reduces tumor burden in vivo.…”
Section: Discussionmentioning
confidence: 61%
“…CLL-1 is another potential molecular target for CAR-T cell therapy as CLL-1 is expressed on AML including leukemia stem cells [ 85 ]. A case study by Zhang et al reported that secondary AML patient treated with anti-CLL CAR-T therapy achieved minimal residual disease (MRD) negative CR that lasted for 10 months [ 83 ]. In another study, two patients treated with CLL-1 and CD33 dual targeting CAR-Ts achieved MRD-negative CR within three weeks [ 84 , 85 ].…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…Another promising target for AML lies with the investigation of C-type lectin-like molecule-1 (CLL1) as a target highly expressed on AML stem cells and blasts but not on healthy HSCs. The first human use of anti-CLL1 CAR T-cells in a pediatric patient with relapsed AML was reported in 2020 [ 135 ]. The patient received an infusion of anti-CLL1 CAR T-cells after lymphodepleting chemotherapy, with adverse effects including transient hypotension and grade I-II cytokine release syndrome.…”
Section: Cellular and Vaccine Therapies For Mds And Amlmentioning
confidence: 99%
“…The patient received an infusion of anti-CLL1 CAR T-cells after lymphodepleting chemotherapy, with adverse effects including transient hypotension and grade I-II cytokine release syndrome. The patient achieved complete remission, which was maintained nine months post-therapy, at the time of the paper submission [ 135 ].…”
Section: Cellular and Vaccine Therapies For Mds And Amlmentioning
confidence: 99%